Danske kortsamlere og -samlinger med fokus på Det Kongelige Biblioteks kortsamlinger - Dupont, Henrik (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2015)
Map collectors have until now been neglected by Danish authors, and we accordingly lack knowledge of the provenance of the older sections of the map collections. The article article gives an overview of the provenance of some of the larger atlases together with a brief description of their contents. The provenance of the large atlas works “Atlas Major” and “Holsteins Atlas” is shown to be an auction purchase of 1813. It also gives an outline of other composite works as well as an account of one of the more recent map collections, acquired by The Royal Library in 1909, the so-called Gjorslev collection, built up by P.B. Scavenius through purchases from Colonel Keyper and later acquisitions. In 1894 the collection was sold to the wholesaler Vilh. Borgen, whose heirs sold it to The Royal Library.